Demandas escolares de adolescentes participantes do Programa de Extensão Janela da Escuta da Faculdade de Medicina da Universidade Federal de Minas Gerais: contribuições da psicopedagogia no acolhimento e na avaliação interdisciplinar - Márcia Zakur Ayres (2021)
This dissertation aims to discuss school demands, selected and evaluated by the psychopedagogist researcher and directed to the Projeto Janela da Escuta, which is part of the Extension Program of the Medical School at the Federal University of Minas Gerais. The participation of a psychopedagogist on an interdisciplinary team of adolescent health care intends to promote the knowledge of the praxis of the psychopedagogical care in hospitals, specifically in the outpatient context. The significant number of adolescents who seek health services, with complaints of frequent difficulties in the learning process, low school performance and behavioral issues, justifies this study. The psychopedagogical work was developed with referral reports, data collecting by anamnesis and the participation of the researcher in experiences in the clinic. The study was based on active listening, psychopedagogical tests and materials, on the results of the evaluations carried out, feedback and on the guidelines for adolescents, their families and other guardians, as well as for the schools they attend. Interdisciplinarity, based on the actions of specialists in adolescent care and listening to the adolescent, as a specialist in himself, is the axis of the project. It also guides the clinical cases hereby presented and the construction of this action research. The participation of psychopedagogists in health care teams contributes to the integral health of adolescents and to the prevention of violence, exclusion or non-inclusion of those with school demands related to not learning well. Besides, it pursues patient/student adherence to being responsible for their school health success, as well as the understanding and participation of the responsible adults throughout the process. In addition to its significant social relevance, this research contributes to the evolution of the knowledge about Psychopedagogy and its role in the outpatient/hospital context.